DETERMINATION OF VOLUMES OF MELT AND SLAG DURING MELTING IN THE ORE-THERMAL FURNACE (Modern Problems of Metallurgy, 2020)
Analysis of recent research and publications. Problematic issues of theory and technology of production of ferroalloys, improvement of structures of ore-thermal electric furnaces, optimization of electric modes of melting are constantly discussed at the relevant international congresses. For a more accurate reflection of the actual physical processes occurring in the working space of the bath, it is necessary to take into account that when the mixture is heated its density changes and occurs between the phase transition.The aim of the study. The purpose of this work is to simulate the process of transition of the charge in the melt, with the subsequent possibility of more accurate determination of some its parameters in the dynamics.Presentation of the main research material. Bath OTF is complex in its structure. It contains a mixture of various physical and chemical conditions (from solid pieces to doughy magma), slag and metal. The physical processes that take place are very different. Some of them are continuous, and others, which are carried out before full melting of single-loaded materials.In order to simulate the process of formation of a melt in a bath of an ore-thermal furnace it is proposed to break its inner space into elementary volumes. We have chosen and slightly modified the method based on the system of cylindrical coordinates, according to which the furnace bath is regarded as a cylinder. We will place further calculation points in the geometric centers of these volumes.The transition of the charge from the solid to the liquid phase is determined by the temperature at which the melting of different types of ferroalloys occurs. If this is the case, knowing the mass and density of the liquid melt and slag at a given temperature, we calculate their real volume, obtained as a result of these phase transitions, in one elementary volume. Thereafter, the total melt volume and charge formed over a given period of time is calculated.During the phase transition, the charge is converted into a melt and slag resulting in its settling down to the bottom of the ore-thermal furnace bath. The maximum permissible amount of charge settling near the electrodes is strictly regulated by the technical documentation of the furnace, so if the calculated value has reached this value, the charge of the charge under the electrodes should be made.It is also possible to compare the calculated volume of the formed melt over the melting interval with its predetermined value. If these indicators are already the same, then it is necessary to merge the melt and slag, otherwise we go to the next period of time and perform these calculations until the specified condition is fulfilled.Conclusions. With a comprehensive approach to the process of modeling the operation of OTF, one of the tasks is to determine the amount of molten metal in the bottom of the bath. This question is solved by the presented methodology and algorithm, which give an opportunity to find out how much melt there is at one or another time during the operation of the furnace.
Keywords: ore-thermal furnace, ferroalloys, charge, fusion, melting temperature, elemental volume